Process development for adoptive cell therapy in academia: a pipeline for clinical-scale manufacturing of multiple TCR-T cell products - Silva, Daniela; Chrobok, Michael; Rovesti, Giulia; Healy, Katie; Wagner, Arnika Kathleen; Maravelia, Panagiota; Gatto, Francesca; Mazza, Massimiliano; Mazzotti, Lucia; Lohmann, Volker; Sällberg Chen, Margaret; Sällberg, Matti; et al. (Frontiers in immunology, 2022)
Cellular immunotherapies based on T cell receptor (TCR) transfer are promising approaches for the treatment of cancer and chronic viral infections. The discovery of novel receptors is expanding considerably; however, the clinical development of TCR-T cell therapies still lags. Here we provide a pipeline for process development and clinical-scale manufacturing of TCR-T cells in academia. We utilized two TCRs specific for hepatitis C virus (HCV) as models because of their marked differences in avidity and functional profile in TCR-redirected cells. With our clinical-scale pipeline, we reproduced the functional profile associated with each TCR. Moreover, the two TCR-T cell products demonstrated similar yield, purity, transduction efficiency as well as phenotype. The TCR-T cell products had a highly reproducible yield of over 1.4 × 109 cells, with an average viability of 93%; 97.8-99% of cells were CD3+, of which 47.66 ± 2.02% were CD8+ T cells; the phenotype was markedly associated with central memory (CD62L+CD45RO+) for CD4+ (93.70 ± 5.23%) and CD8+ (94.26 ± 4.04%). The functional assessments in 2D and 3D cell culture assays showed that TCR-T cells mounted a polyfunctional response to the cognate HCV peptide target in tumor cell lines, including killing. Collectively, we report a solid strategy for the efficient large-scale manufacturing of TCR-T cells.
Gesehen am 29.07.2022